Skrining faktor risiko prediabetes yang dapat dimodifikasi di komunitas - Liberty, Iche; Idris, Fachmi; Pariyana, Pariyana; Mariana, Mariana; Septadina, Indri Seta; Utama, Meria; Irsan, Irsan; Nurrahman, Muhammad Irfian; Putra, Muhammad Rafi (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2022)
Prediabetes is the best period to prevent and or delay the conversion of glucose status to diabetes, but it is very progressive to develop complications in the future. Screening can be an effort to prevent and increase awareness of prediabetes. The purpose of this activity is to describe the results of screening for modifiable prediabetes risk factors in the community in the working area of Puskesmas Talang Ratu. This community service activity is carried out by screening and providing brief education to the community using flyers and information delivery assistance by the Puskesmas. A total of 33 respondents voluntarily participated in this activity. The results of the screening become a reference for individual education. Based on the screening carried out, the results showed that the average age of the respondents was 50.33 years and the majority were female (69.70%), the last education was high school and civil servant occupation (48.48%). The distribution of smoking behavior was 12.12%, and the majority (54.55%) of respondents have the habit of eating vegetables 7 times a week. Then 42.42% of respondents have the habit of eating fruit 7 times a week. The average systolic was 133.90 ± 17.25 mmHg and the diastolic was 82.57 ± 9.35, the average total cholesterol was 243.90 ± 239.48. The average BMI of respondents was 26.10 ± 3.97 and the average waist-hip circumference ratio was 0.86 ± 0.064. Meanwhile, the average blood glucose was 114.42 ± 63.97. The results of the screening also obtained that the average time spent doing activities in a sitting, lying, or lying position was 4.97 hours with a range of 1-12 hours.